Solid solution strengthening and phase transformation in high-temperature annealed Si80Ge20 alloy - Chiang, Tun-Yuan; Wen, Hua-Chiang; Chou, Wu-Ching; Tsai, Chien-Huang (My University, 2014)
This investigation demonstrates the temperature-dependent mechanical properties of Si80Ge20 alloy films via a nanoindenter in the indentation depth of 100 nm. The roughly equal root mean square roughness (R-rms) values and repeatable load-displacement (P-delta) curves for the samples ensure the mechanical performances mainly contributed from the influences of annealing temperatures. The hardness (H) values of samples increase with the temperatures of an initial annealing in the range from RT to 900 degrees C, and, conversely, decrease for annealing temperatures over 900 degrees C. Accordingly, both E/H and h(r)/h(max) values, exhibiting an inverse tendency in the above temperature range, hints that the solid solution strengthening effect and the softening phenomenon occur for the initial-annealing and over-annealing stages, respectively. In addition, grazing incidence X-ray diffraction (GIXRD) analysis demonstrates the lattice expansion and the broadened peak that attribute to the solid solution strengthening of samples and the segregation of Ge, respectively. Through observing the value of the (200) lattice spacing of 5.624 A for a 900 degrees C-annealed sample by transmission electron microscopy (TEM) analysis, it is verified that the segregation of Ge is responsible for the decreased hardness for the 1000 degrees C-annealed sample. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Characterization; Crystal structure; Semiconducting silicon compounds